The Enablers And Inhibitors Of Adopting Internet-Based Electronic Commerce: A Survey Of A Sample Of Malaysian Businesses - Ramazan, Lupupa Samson (2000)
The Multimedia Super Corridor (MSC) , a major electronic commerce infrastructure, which is a government push towards the realisation of Vision 2020, is aimed at moving Malaysia into the information age. Through the MSC, the government is trying to push the electronic commerce to equal other developed nations who are already in the system. Thus, since the inception of the MSc, Malaysian businesses have been encouraged to adopt this new platform of business, especially the Internet. The purpose of this study is to examine the enablers and inhibitors in adopting Internet-based electronic commerce by Malaysian businesses. A survey method was used to collect data and the data were analysed using statistical techniques. The Statistical Package for Social Science(SPSS) was used to analyse the data collected. The study was done using a sample of Malaysian businesses. The results of this study indicate that businesses have been using the Internet for their businesses in some ways. The Internet is being used for communication via email, advertising, promotion, and providing customer services. However, the Internet is not highly used in the buying and selling products. Analysis done in different demographic groups shows that there is a difference on some variables of Internet usage by businesses. Advertising composed an overwhelming percentage of Internet usage when compared with other uses of the Internet. The key enablers emerging from the analysis in this study for Internet adoption are: businesses feel that conducting business on the Internet could create direct and indirect marketing; Internet technology is perceived to be a good investment in the coming millennium; conducting business on the Internet would allow a company to cross international boundaries; there is wider corporate exposure in conducting business on the Internet; Internet is believed to be the cheapest communication medium. However, there are some inhibitors identified as far as the adoption of Internet for business is concerned. There is lack of security on the web, that is, the information dissemination online does not seem to have much protection from being tempered; there is a problem of technical knowledge for companies to do business on the Internet; overloaded communication lines is also a draw-back in the Internet usage; businesses fear that Internet business allows other competitors to spy on other companies' products and their price list; some feel Internet business should only be conducted between business-to-business rather than business-to-individuals. Businesses on the Internet could be more effective if the policy makers are aware of the push factors and top management are more knowledgeable about the hardware and software of the Internet business. The introduction of National Electronic Commerce Committee (NECC) in malaysia, a government taskforce, is expected to further push towards the adoption of electronic commerce in Malaysian businesses.